2021
DOI: 10.1111/phn.12995
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian fathers’ experiences with a home visiting program

Abstract: Objective To explore fathers’ experiences with a Norwegian home visiting program during the prenatal period and the first‐year postpartum. Design Qualitative design with interpretive description (ID) as the methodological approach. Sample Individual interviews with fathers (n = 13) who received home visits by a public health nurse (PHN) within the New Families home visiting program. Measures Interviews were guided by a semi‐structured interview‐guide, which contained open‐ended questions encouraging informants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…In some situations, they saw how the father-to-be had a central role in facilitating a good dialogue in the meeting. In other situations, his role did not function as well, maybe because he seemed nottobesureaboutwhatwasexpectedofhiminahomevisit.This corresponds to the results in a recent interview study by Solberg et al (2021). Another study revealed that fathers usually had few expectationsforthePHNs'homevisits.Moreover,afterthehome visits they often felt disappointed and left alone (Solberg & Glavin, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In some situations, they saw how the father-to-be had a central role in facilitating a good dialogue in the meeting. In other situations, his role did not function as well, maybe because he seemed nottobesureaboutwhatwasexpectedofhiminahomevisit.This corresponds to the results in a recent interview study by Solberg et al (2021). Another study revealed that fathers usually had few expectationsforthePHNs'homevisits.Moreover,afterthehome visits they often felt disappointed and left alone (Solberg & Glavin, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The home visit was also considered a good way to get to know each other and prepare the ground for further cooperation. These findings are supported by studies of parents' experiences of homecare, showing that mothers and fathers felt safe in their own home environment, indicating that it might be easier for health personnel to provide high‐quality care that optimises the health and well‐being of the whole family unit by providing home‐based early postnatal care [47–49].…”
Section: Discussionmentioning
confidence: 83%
“…New fathers who were present during home visits by a public health nurse, in a recent study from Norway, often felt that their perspectives were not sufficiently included. They would have liked more attention as fathers and an opportunity to talk about their experiences independently (Solberg et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The conversation with the CHS nurse was perceived as helpful in normalizing their feelings, which could be a relief, and some fathers also found new ways of interacting with their child. Solberg et al (2022) found that a conversation about the fathers' own role and the strong bond between mother and child, which the fathers had not been prepared for, was helpful for fathers in finding their place and role in the family. In a review of new fathers' experiences and needs, Venning et al (2021) found that fathers could experience their various roles and ambitions as overwhelming, for example, to be informed, active and successful in caregiving, and supporting their partners, which was why easy access to support and help in normalizing their experiences was considered important (Venning et al, 2021).…”
Section: Discussionmentioning
confidence: 99%